Patients’ attitudes towards cancer screening: a literature review - Rybin, A.; Zamyshlyak, V. (Journal of Education, Health and Sport, 2026)
The aim of this review is to summarise the findings of studies on patients’ attitudes towards cancer screening. The review examined the full texts of 63 publications on four common cancers: breast cancer, cervical cancer, colorectal cancer and lung cancer. For each disease, specific features of patients’ attitudes towards screening programmes were identified, as reflected in their willingness to undergo screening, their awareness of the disease and screening for it, and the motivators and barriers to participating in cancer screening. For all these diseases, widespread support for screening programmes was found among various population groups, but the awareness of this support is called into question. The review concludes with recommendations for conducting research into patients’ attitudes towards cancer screening in Ukraine.